A better globalization : legitimacy, governance, and reform - Dervis, Kemal; Ozer, Ceren; Center for Global Development (Washington, D. C. : Center for Global Development, 2005)
'Discusses the two broad dimensions of the globalization debate -- economic, including finance, trade, poverty, and health ; and political, covering security, the fight against terrorism, and the role of international institutions -- and the significance of democratic consent in the twenty-first century' -- Provided by publisher
Includes bibliographical references (p. 273-[288]) and index.
Keywords: Globalization